2021
DOI: 10.1101/2021.07.23.21260716
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Associated Hepatitis in Children (CAH-C) during the second wave of SARS-CoV-2 infections in Central India: Is it a complication or transient phenomenon

Abstract: Background: Besides Covid-19, SARS-CoV-2 infection has been associated with Multiple Inflammatory Syndrome in children (MIS-C). However, a unique presentation of a transient form of hepatitis in pediatric age group occurring subsequent to the asymptomatic SARS-CoV-2 infection is yet to be reported in children. Presently the clinical work, temporal association and characteristics different than MIS-C of the cases of CAHC is being dealt with. Methods: As a retrospective and follow up observational study we revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…18 However, when one considers both evidence of acute and previous infection, the strength of association may increase. In a preprint from India, 19 among 37 cases of hepatitis between April -July 2021, all were either infected with or had prior evidence of SARS-CoV-2 infection. Furthermore, from the European surveillance data, while serology results were only available on 26 cases, 19 (73.1%) were seropositive.…”
Section: Evidence For Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“…18 However, when one considers both evidence of acute and previous infection, the strength of association may increase. In a preprint from India, 19 among 37 cases of hepatitis between April -July 2021, all were either infected with or had prior evidence of SARS-CoV-2 infection. Furthermore, from the European surveillance data, while serology results were only available on 26 cases, 19 (73.1%) were seropositive.…”
Section: Evidence For Sars-cov-2mentioning
confidence: 99%
“…19,25 A preprint report of a nationwide (US) retrospective cohort study from March 11, 2020 to March 11, 2022 of 245,675 children with a history of COVID-19 (≤10 years old, mean age: 6.0 ± 3.1 years),26 found that children with COVID-19 had a higher risk of elevated AST or ALT (hazard ratio [HR]: 2.52; 95% confidence interval [CI]: 2.03-3.12) and bilirubin (HR: 3.35, 95% CI: 2.16-5.18) at six months after infection compared with a propensityscore matched cohort of those with other respiratory virus infections (n= 245,161).…”
mentioning
confidence: 99%
“…1,2 Early evidence from a study in India described 37 pediatric patients presenting with clinical signs of hepatitis after having COVID-19, but how COVID-19 affects the liver in pediatric patients remains unknown. 3 Recently, the Centers for Diseases and Control released a nationwide health alert about an increase in hepatitis cases of unknown origin in children, raising concern about potential sequelae of COVID-19 infection. 4 In this study, we test whether there was increased risk of elevated serum liver enzymes and bilirubin following COVID-19 infection in children.…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility is both adenovirus and coronavirus infecting the same child may lead to a totally different virus that has not been detected yet ( https://theconversation.com/hepatitis-cases-are-increasing-among-children-in-the-uk-could-covid-have-a-role-to-play-181303 ). A recent study from India suggested that either the Delta variant or its interaction with adenovirus or newer recombinants of Delta variant may possibly be associated with pediatric hepatitis which needs urgent and thorough investigations [ 10 ]. Another possible reason is autoimmune hepatitis (the body itself attacks the liver); however it is also a rare condition that is causing a cluster of cases in children.…”
mentioning
confidence: 99%
“…Some asymptomatic SARS-CoV-2 infection in children or adolescents (n = 33) developed into acute hepatitis with no history of pre-existing liver disease. The patients (n = 8) with MIS having a high level of inflammatory markers which required admission to critical care, and three patients had an adverse outcome [ 13 ]. Pessoa and his coworkers have reported the first case of hepatitis in a male child infected with SARS-CoV-2 that has the Toll-like receptor 7 (TLR-7) Gln11Leu single nucleotide polymorphism, which could impair an efficient initial immune response [ 14 ].…”
mentioning
confidence: 99%